Making a Low-Cost Soda Can Ethanol Burner for Out-of-Laboratory Flame Test Demonstrations and Experiments - Lee Yu, Henson L (Archīum Ateneo, 2015)
This article demonstrates how to make a low-cost ethanol burner utilizing soda cans. It burns with a light blue flame suitable for out-of-laboratory flame test demonstrations where interference from a yellow flame needs to be avoided.